2018
DOI: 10.1080/17437199.2018.1457449
|View full text |Cite
|
Sign up to set email alerts
|

Network meta-analysis in health psychology and behavioural medicine: a primer

Abstract: Progress in the science and practice of health psychology depends on the systematic synthesis of quantitative psychological evidence. Meta-analyses of experimental studies have led to important advances in understanding health-related behaviour change interventions. Fundamental questions regarding such interventions have been systematically investigated through synthesising relevant experimental evidence using standard pairwise meta-analytic procedures that provide reliable estimates of the magnitude, homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…This study is registered with PROSPERO [21] (International Prospective Register of Systematic Review) (CRD42015023541) and is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is registered with PROSPERO [21] (International Prospective Register of Systematic Review) (CRD42015023541) and is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [22].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were done in accordance with our registered protocol (PROSPERO: CRD42015023541) [21]. We conducted meta-analyses according to time point of outcome measurement (≤6 months, 6–12 months, last follow-up) for sexual health outcomes (i.e., percent engaging in condomless sex) and drug risk outcomes (i.e., percent engaging in injection drug risk or other drug risk behaviours).…”
Section: Methodsmentioning
confidence: 99%
“…Network meta-analysis (NMA) is an extension of pairwise meta-analysis that is increasingly used in health research [ 15 , 16 ]. It enables the simultaneous comparison of multiple intervention strategies and their ranking according to their relative effects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As NMA allows the comparison and ranking of multiple treatment strategies simultaneously, it is ideal to inform clinical decision‐making in circumstances where a choice needs to be made among multiple interventions 2 . Over the last two decades, the developments of NMA methodologies and relevant software packages 3,4 have further increased the popularity of NMA in a variety of disciplines 5–9 . Reporting guidelines for NMA have been developed to improve the reporting of systematic reviews incorporating NMA 10 and the latest Cochrane handbook edition includes a chapter on conducting NMA 11 …”
Section: Introductionmentioning
confidence: 99%